Роль змішаного навчання при підготовці фахівців - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2023)
Резюме. У статті представлено технологію змішаного навчання як різновид методики навчання, яка реалізує принципово нові методи та форми навчання, використовуючи інформаційно-комунікаційні засоби реалізації. Розглянуто освітню онлайн-платформу Moodle (модульне об’єктно-орієнтоване динамічне навчальне середовище), безкоштовну, відкриту (Open Source). Виокремлено ключові особливості змішаного навчання.

Abstract. The article presents the technology of blended learning as a type of learning methodology that implements fundamentally new methods and forms of learning, using information and communication means of implementation. The most famous in Ukraine educational online platform Moodle (modular object-oriented dynamic learning environment), free, open (Open Source) was considered. Blended learning involves reducing the number of classroom classes by transferring part of the classes to an electronic environment. At the same time, the ratio of classroom (traditional) and virtual (electronic) components may differ and depends on a large number of factors: subject area, age of students, level of training of students, technical infrastructure for training. The key features of blended learning are highlighted. Considering the content of blended learning, it is emphasized that it consists of the following components: traditional classroom classes; independent work of education seekers in the electronic environment; group e-learning (online conferences, etc.). The concept of «flipped classroom» («inverted class») is recognized as a key concept of blended learning, in which special attention is paid to both the design aspects of electronic courses and the aspects of the organization of the educational process. A perspective for further research is the use of training programs that allow each student to study in a convenient mode. Considering the content of blended learning, it is important to emphasize that it consists of the following components: traditional classroom classes; independent work of students in the electronic environment; group e-learning (online conferences, etc.) The key concept of mixed learning is the concept of «flipped classroom», in which special attention is paid both to the design aspects of electronic courses and to the aspects of the organization of the educational process. Regarding the organization of the educational process. The essence of «inverted technology» is to rearrange the key components of the educational process based on the active use of the electronic learning environment. Under the conditions of the implementation of «inverted technology», the educational process begins with the setting of a problematic task, for the fulfillment of which the student is forced to familiarize himself with the material placed in the electronic course environment. At the same stage, a self-monitoring of understanding of the material is carried out in the electronic environment. Thus, the process of assimilation of new material begins with the independent work of students. A properly designed electronic course for blended learning facilitates the individualization of the learning process (allows to take into account the individual learning style of students: level, type of cognitive abilities, speed of mastering the material), ensures more active involvement of students in educational activities, and improves success in general. provided the proper organization of mixed learning and a reasonable ratio of classroom classes with independent work, the quality of learning in modern conditions will only increase.
The role of blended education in the training of specialists
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00011317
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-3
Keywords: змішане навчання; технологія змішаного навчання; компоненти; фактори; інформаційно-комунікаційні засоби реалізації; електронні курси